Pengembangan Pengetahuan Masyarakat Tentang Pembuatan MP ASI Berbasis Panganan Lokal dengan Metode Demonstrasi - Supiana, Nia; Herni Sulastien; Kusumawardani, Diny; Kamila, Nurul Auliya; Daniaty, Asri; Aisyah, Siti; Wardani, Yulia indah; Wijaye, I Wayan Arte; Oktaviani, Fitria Deva; Yupita, Baiq (PT.Mantaya Idea Batara, 2023)
ne of the efforts to improve children's health and nutrition is to provide the best food for Baduta. If infants and children aged 6-24 months do not get enough nutrition from complementary feeding, it will result in impaired growth and malnutrition. Guntur tiger village is one of the fostered villages of FIK UNW Mataram. Based on the results of the nutritional assessment of Toddlers that was carried out previously, it turned out that several nutritional problems were still found, especially in the Baduta age group. Namely, the increasing incidence of stunting. The main cause is the limited knowledge of mothers about Baduta nutrition and mother's skills in preparing food to meet nutritional needs with locally available food. Community Service Activities, providing health education about nutrition and making MPASI based on local food for mothers pregnant women, cadres and Mrs. Baduta was held on March 25, 2022. The activity was carried out at the Guntur Macan village hall with 28 participants. The results of the final evaluation of the increase in knowledge and skills of participants by 51.0%. To form good nutritional behavior in families, sustainable mentoring activities are needed.